Enhanced arsenic removal by hydrothermally treated nanocrystalline Mg/Al layered double hydroxide with nitrate intercalation - Goh, Kok Hui (2011)
A nanocrystalline Mg/Al layered double hydroxide (FCHT-LDH) adsorbent was developed and investigated through stoichiometric calculations, nitrate displacement investigation, comprehensive sorption/desorption experiments, and analyses with XPS, XRD, FTIR, CHNS/O, and EDX for better understanding of the predominant nature of arsenate (As(V)) interaction with FCHT-LDH. FCHT-LDH demonstrated a higher sorption capacity and a faster sorption rate compared to the layered double hydroxides (LDHs) prepared by conventional methods, due to its higher surface area, better porosity characteristics, and nanocrystalline property. These results also indicated the important role of hydrothermal treatment during the synthesis process for enhanced As(V) removal. The observed nitrate−arsenate molar displacement ratio, increased interlayer spacing, and decreased nitrogen content in the interlayer region revealed the predominance of anion exchange mechanism in As(V) sorption by FCHT-LDH. However, a slight pH increase during As(V) sorption equalization and the presence of ca. 25% irreversibly sorbed As(V) signified the occurrence of ligand exchange process as the secondary sorption mechanism. This specific sorption process that possibly involved formation of inner-sphere As(V) complexes with a monodentate mononuclear configuration at the aluminum center, rendered the FCHT-LDH a high affinity for As(V) over nitrate but induced hysteretic sorption/desorption characteristic that limited its regenerated sorption capacity.